Developing the Character-Based Students Worksheet of Science with Inquiry Model for Students of Grade IX - Melkyanus Kaleka; Yasinta E. Ika (Universitas Negeri Yogyakarta, 2018)
Student Worksheet (LKS) is a learning media as a means to train the students to think, act and having an attitude like a young scientist. The purpose of the particular study was to produce a character-based LKS of Science with inquiry model and analyzing the development of the LKS on students’ achievement and character. This research was a developmental research. The research sample was the students of class IXa as the experimental class and students of class IXd as the control class. The sampling technique used purposive sampling. Research procedures were; introduction, design, and development. Data collection techniques were the questionnaire, test, and documentation. Data analysis techniques used the percentage, t-test, and gain test. The results of the analysis concluded that the character-based Students Worksheets with inquiry model was very feasible to be used as a learning guide for a science subject. There is a significant difference in learning achievement between students in the experimental class and students in the control class.